Burundi : Joint Staff Assessment of the Interim Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2004)
The poverty reduction strategy program summarizes the current state of knowledge on poverty in Burundi derived from the participatory process and national consultations. The paper describes Burundi's serious poverty situation and presents a sound poverty reduction strategy that is integrated into the immediate post-conflict priorities stemming from the Arusha agreement. Peace and democratic governance; reintegration of conflict victims and disadvantaged groups into the economy; private sector development; issues on human capital; HIV/AIDS-related issues; and advancing the role of women in development are the priority areas.